MRI ASSESSMENT OF THE NEUROLOGICAL AND PSYCHOLOGICAL STATE OF WOMEN WITH CANCER OF THE REPRODUCTIVE SYSTEM - Jurayev Shohruh Jumanazarovich (World Scientific Research Journal, 2025)
Abstract: This study examined the neurological and nosogenic psychopathological conditions of women with cancer of the reproductive system, as well as the analysis of magnetic resonance imaging (MRI) of the brain. The purpose of the study is to identify neurological disorders and psychopathological symptoms associated with cancer, as well as to analyze their impact on the structure of the brain. Morphological changes in the brain, especially pathologies associated with stress and psychopathology, were studied using magnetic resonance imaging. The obtained data can contribute to a better understanding of the neurological and psychopathological conditions of women with cancer of the reproductive system in clinical practice and the improvement of treatment.